Análise da qualidade e reúso da água em tanques de refrigeração de leite - Nascimento, Genifer Reis do (2021)
Water is the most important and indispensable natural resource for maintaining life. In dairy establishments it is of great importance, since, in addition to serving as a drink for animals, it is also used throughout the maintenance and cleaning process. Thus, the quality of the water used in the equipment and in the handling is of great importance for obtaining good quality milk that meets the standards required by the legislation. Furthermore, it is important to treat these wastewater, that is, effluents generated in the tanks of milk cooling, as they influence the processing of milk, in addition to bringing benefits to the environment by reducing water waste. Thus, this work sought to evaluate the quality of the water used in cleaning the milk cooling tanks, as well as analyzing the perception of rural owners about the importance of water quality and reuse in cleaning those tanks. The study was developed in Rio Grande do Norte in 14 municipalities, divided by groups, with a total of 27 individual tanks. The water analysis was carried out on only one property. Data from this work were analyzed using means and deviations, and differences obtained by Duncan's test. Among the 27 tanks, 50% had a cleaning score of 3 (poor), 33.3% good and 16.67% very good. About the knowledge of cleaning the tanks, 51.86% of the producers had very good or good knowledge, and 48.15% had bad knowledge. Only 25.93% of owners use sanitation methods. Therefore, with the results obtained it is possible to conclude that the farmer's knowledge of cleanliness is fundamental to guarantee the quality of the milk during the storage process. Furthermore, the more knowledge the producer has about cleaning, the better the results of using cleaning methods. However, it is still necessary to continue the research, in relation to the perception of producers about the importance of reusing water.